Effects of homobrassinolide in barley callus culture - A. Temel; N. Gozukirmizi (Plant, Soil and Environment, 2012)
Thirty-day-old barley (Hordeum vulgare L. cv. Zafer-160) calli were treated with 0, 0.5, 1 µmol/L 22(S),23(S)-Homobrassinolide (HBL) for four weeks. Transfer of calli to hormone-free or HBL-supplemented medium caused an increase in total soluble protein and DNA contents and a decrease in superoxide dismutase (SOD; E.C. 1.15.1.1) activity. 0.5 µmol/L HBL caused the highest protein and DNA levels and the minimum decrease in fresh weight; while the lowest superoxide dismutase activity was recorded in 1 µmol/L HBL-treated group. Calli developed nodular structures and green cell clusters after transfer onto hormone-free or HBL-supplemented medium. Methylation-sensitive restriction fingerprinting (MSRF) analysis detected a few changes in methylation between control and 0.5 µmol/L groups. Combination of data led us to the conclusion that HBL favoured regeneration and shoot development and may ameliorate tissue culture stress in a mechanism, which is independent of cytosine methylation.